Post-fire mechanical behavior and recovery of structural reinforced concrete beams - Akca, Abdullah Huzeyfe; Ozyurt, Nilufer (ELSEVIER SCI LTD, 2020)
The results of fire tests obtained from small-sized specimens may fail to represent the real post fire behavior of structural elements. Therefore, in this study structural concrete beams were exposed to ISO fire curve and then subjected to different curing conditions to better understand the changes in concrete during the post-fire stage. Beams were tested under four-point bending to evaluate their residual mechanical performance, and scanning electron microscopy (SEM) was performed in order to monitor the changes in the morphology of concrete due to fire exposure. The results showed that high temperature exposure caused deterioration in the morphology and reduction in residual mechanical properties of concrete, while post-fire re-curing caused an improvement in residual mechanical properties and recovery in the microstructure. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: High temperature; Structural reinforced concrete beam; Recovery; Deterioration; Microstructure; HIGH-PERFORMANCE CONCRETE; COMPRESSIVE STRENGTH; CEMENT PASTE; TEMPERATURE; Construction & Building Technology; Engineering; Materials Science